2015
DOI: 10.1177/0883073815620674
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Basal Ganglia Stroke and its Association with Trivial Head Trauma

Abstract: This study explored the clinical profile, risk factors, neuroimaging and outcome of childhood basal ganglia stroke. Children (6 months-12 years) with basal ganglia stroke registered between 2007-2011 were retrospectively enrolled, while newly diagnosed cases over the 2-year study period were enrolled prospectively. Children with recent trivial head trauma were compared with those without it. Of the 35 children enrolled, trivial head trauma was seen in 74%. The non-trivial head trauma group (n = 9) comprised un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…Prashant Jauhari el al. hypothesized that transient vasospasm secondary to trauma-induced stretching of lenticulostriate vessels may have led to a more favourable outcome in these children 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Prashant Jauhari el al. hypothesized that transient vasospasm secondary to trauma-induced stretching of lenticulostriate vessels may have led to a more favourable outcome in these children 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Basal ganglia infarction in infants after mild head trauma has been reported in several case reports and case series over the last decades. [1][2][3][4][5][6][7] The pathogenesis of this phenomenon remains to be elucidated. It was Kaya et al 18 who reported first on four children (age 9 months-3.5 years) with basal ganglia infarction and basal ganglia calcification.…”
Section: Discussionmentioning
confidence: 99%
“…However, these authors did not mention an association with trauma, and the key aspect was a radiological message and not a clinical one. Jauhari et al 7 analyzed 48 children (median age 18 months) with basal ganglia stroke, and 26 of them had a history of trivial head trauma. Although all of the children underwent an initial CT scan, basal ganglia calcification was not seen in any of them.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the Indian context, perinatal–neonatal event remains the predominant cause of intellectual disability, irrespective of endemicity for a large number of infections including T. solium . [ 15 ]…”
Section: Discussionmentioning
confidence: 99%